Computational Methods for Molecular Understanding of the Antibiotic‐Aminoacyl tRNA Synthetase Interaction. Issue 3 (9th March 2023) - Chowdhury, Shilpi; Ghosh, Poulami; Nandi, Nilashis
Abstract: Developing an understanding of the interactions between an antibiotic and its binding site in a pathogen cell is the key to antibiotic design—an important cost‐saving methodology compared to the costly and time‐consuming random trial‐and‐error approach. The rapid development of antibiotic resistance provides an impetus for such studies. Recent years have witnessed the beginning of the use of combined computational techniques, including computer simulations and quantum mechanical computations, to understand how antibiotics bind at the active site of aminoacyl tRNA synthetases (aaRSs) from pathogens. Such computational protocols assist the knowledge‐based design of antibiotics targeting aaRSs, which are their validated targets. After the ideas behind the protocols and their strategic planning are discussed, the protocols are described along with their major outcomes. This is followed by an integration of results from the different basic protocols. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Analysis of active‐site residues from primary sequence of synthetase and transfer RNAs Basic Protocol 2 : Molecular dynamics simulation‐based protocol to study the structure and dynamics of the aaRS active site:antibiotic complex Basic Protocol 3 : Quantum mechanical method‐based protocol to study the structure and dynamics of the aaRS active site:antibiotic complex